Guajará-Mirim (Estado de Rondônia - Brasil) e Guayaramerín (Departamento de Beni - Bolívia): avaliação documental para verificar a possibilidade de desenvolvimento territorial e turismo - Silva, Ana Leopoldina da (2021)
This dissertation evaluated the potential on performing territorial development and tourism in the municipalities of Guajará-Mirim (State of Rondônia - Brazil) and Guayaramerín (Department of Beni - Bolivia), thus, the specific objectives were defined: to screen the bibliography on territorial development and tourism, to contextualize the constitution of twin cities from the 17th to the 21st century, and to evaluate guiding documents for territorial development and tourism in municipalities of the 21st century. For this purpose, bibliographic and documentary materials were used, such as historical and ecclesiastical literature, books of scientific knowledge, government reports from the Morsing Committee, international reports from the World Tourism Organization and the European Union, guiding documents available on government platforms such as the Ministry of Tourism, Rondônia State Secretariat for Tourism, Guajará-Mirim City Hall, Chico Mendes Institute for Biodiversity Conservation, State Secretariat for Planning, Budget and Management - Rondônia, Municipal Autonomous Government of Guayaramerín and the Documentation and Information Center of Bolivia. These data made it possible to approach territorial development and tourism, wih theoretical examples to support the needs for changes in contextual practices. In addition, it was reported the Portuguese and Spanish colonizations, native peoples and the construction of the Madeira-Mamoré railway as a landmark of the territorial constitution of the Brazilian and Bolivian municipalities. Both, of these territories correspond to the plans and planning listed and evaluated in the last part of this study.